Implementasi Project-Based Learning dalam Pembelajaran Bahasa Arab: Studi Kualitatif terhadap Maharah Kalam dan Maharah Kitabah - Maharani, Ninda; Prastika, Inka Puji (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
Arabic language learning still faces challenges in developing productive skills, particularly speaking (kalam) and writing (kitabah), which have not been optimized due to the dominance of conventional teaching approaches. Meanwhile, in-depth qualitative studies examining the implementation of Project-Based Learning (PjBL) especially those that integrate these two skills simultaneously remain relatively limited. This study aims to analyze the implementation of PjBL and examine the dynamics of the development of kalam and kitabah skills in Arabic language learning. This study employs a descriptive qualitative approach with data collection techniques including interviews, documentation, and analysis of learning artifacts. The findings indicate that the implementation of PjBL fosters a shift in learning toward a student-centered approach through authentic project-based activities. This approach demonstrates enhanced productive skills, increased self-confidence, and greater student engagement in learning. On the other hand, the implementation of PjBL also faces a number of challenges, such as time constraints, heterogeneity in language proficiency, and complexity in the development of assessment instruments. This study contributes to the development of Arabic language pedagogy by affirming the relevance of PjBL as a contextual approach and the importance of strengthening teacher competencies and institutional support in its implementation